The role of clinical and genealogical study in the examination of patients with chronic venous insufficiency - Kolosovych, I. V.; Korolova, K. O.; Korolova , Z. V. (General Surgery, 2024)
Objective — to demonstrate the role of heredity in the development of varicose veins using a clinical‑genealogical study, analyze family cases of varicose veins of the lower extremities, determine the type of disease inheritance in the examined patients, and assess the possible outcomes of genetic inheritance for their descendants. Materials and methods. The study involved 64 patients, mostly women — 52 (81.3%), with different clinical classes of varicose veins. The clinical‑genealogical method of pedigree analysis was used to establish the type of inheritance. We determined the nature of the disease trait (hereditary or non‑hereditary) and the type of inheritance (autosomal dominant, autosomal recessive, or gender‑linked). Results. Among the 64 examined patients, 28 (43.8%) had familial cases of varicose veins. In our clinical‑genealogical study of the pedigrees of patients with chronic venous insufficiency, we found an autosomal dominant inheritance of this pathology, not linked to gender. Direct inheritance across generations was observed. Conclusions. The analysis of the pedigrees of patients with varicose veins of the lower extremities and other manifestations of chronic venous insufficiency revealed the familial nature of disease inheritance, characterized by an autosomal dominant inheritance type and a high degree of gene expression. In these families, children are more likely to show signs of the disease. A hereditary predisposition to certain forms of varicose veins has also been noted. Consequently, in individuals with reticular varicose veins, the main veins of the lower extremities exhibited no alterations with age, whereas reticular varicose veins simply increased in prevalence.